Generating Orthogonal Voronoi Treemap for visualization of hierarchical data - Yan-Chao Wang; Jigang Liu; Feng Lin; Hock-Soon Seah (CGI 2020: Advances in Computer Graphics, 2020)
A novel space partitioning strategy is presented for implicit hierarchy visualization. The proposed orthogonal Voronoi treemap (OVT) partitions an empty canvas into nested orthogonal rectangles, thus the generated layout is not only flexible to diversified data value, but also much tidier than the Voronoi treemap with nested polygons. To achieve this, we first introduce a new distance calculation strategy in order to generate axis-aligned segmentation among the sites. To cope with the new segmentation strategy, we then design a sweepline + skyline heuristic algorithm to partition the canvas to generate an orthogonal Voronoi treemap. Comparative analyses on the computational experiment results in terms of aspect ratio is discussed.